Screen-based literacy practices in Swedish primary schools - Peter Andersson; Sylvana Sofkova-Hashemi (Universitetsforlaget, 2016)
This paper contributes to the discussion of digital literacies in early literacy education. We focus on the nature of screen-based literacy practices in relation to print-based, paper-pen practices in the early years of schooling when pupils learn to read and write (aged 7-8). Our results show that pupils engage in several diverse screen-based practices, although they are conventional in nature. However, aspects of blogging and tweeting do approach the characteristics of "new literacies" as defined in previous research.